Relationship between FEV1 and PaO2 in Chronic Obstructive Pulmonary Disease (Jalalabad Medical Journal, 2025)
Chronic obstructive pulmonary disease (COPD) is one of the leading causes of mortality and morbidity. Every year, many people suffer from this disease and die prematurely of it or its complications. This cross-sectional study was carried out in the department of physiology at Sylhet MAG Osmani Medical College, Sylhet, from January 2018 to December 2018 in order to find out the relationship between FEV1 and PaO2 in chronic obstructive pulmonary disease. For this purpose, a total of 50 COPD patients were selected from the department of medicine at Sylhet MAG Osmani Medical College, Sylhet. There was a significant positive correlation between FEV1 and PaO2 in COPD (r=0.487; p